Revisiting the putative TCR Cα dimerization model through structural analysis - Wang, Jia-huai; Reinherz, Ellis L. (Frontiers in Immunology, 2013)
Despite major advances in T cell receptor (TCR) biology and structure, how peptide-MHC complex (pMHC) ligands trigger αβ TCR activation remains unresolved. Two views exist. One model postulates that monomeric TCR-pMHC ligation events are sufficient while a second proposes that TCR-TCR dimerization in cis via Cα domain interaction plus pMHC binding is critical. We scrutinized 22 known TCR/pMHC complex crystal structures, and did not find any predicted molecular Cα-Cα contacts in these crystals that would allow for physiological TCR dimerization. Moreover, the presence of conserved glycan adducts on the outer face of the Cα domain preclude the hypothesized TCR dimerization through the Cα domain. Observed functional consequences of Cα mutations are likely indirect, with TCR microclusters at the immunological synapse driven by TCR transmembrane/cytoplasmic interactions via signaling molecules, scaffold proteins and/or cytoskeletal elements.